Human touch versus algorithm: reception of AI poetry among Romanian adolescents - Roiniță, Alina (Frontiers in Education, 2026)
This research paper presents the results of a case study on how Romanian adolescents perceive poetry written by Romanian authors versus poetry generated by an artificial intelligence (AI) model. The study mainly relied on quantitative methods (descriptive statistical analysis using SPSS) and interpretive discussion of trends emerging from the aggregated response data. It involved a control group, which was informed from the beginning about the research variables, including the fact that they would evaluate both human-written poems from various literary movements and AI-generated poems produced using prompts based on texts from the same poetry volumes, and an experimental group, which did not know the texts’ origins. The experimental group was only informed about the origin of the texts at the end, at which point they were invited to re-evaluate the AI-generated poems. The aim of this study is to investigate how adolescents perceive and evaluate human-written poetry from different literary movements compared to AI-generated poetry. The analysis examines differences in emotional responses, perceived creativity and complexity of the poems, and how these perceptions are shaped by the author’s identity (AI or human), as well as by the respondents’ educational background and gender. The main findings reveal that adolescents’ perception of poetry is strongly shaped by authorial labels, with human poems receiving more favourable evaluations when their origin is known. It is worth noting that, in the absence of such information, AI-generated poems were often rated higher than those written by human authors. Once the authorship was revealed, however, AI-generated texts tended to be penalized – especially by female respondents and those with a humanities background – possibly suggesting a stronger attachment to “traditional literature” that influences their reception. Emotional responses also vary with authorship: human poems tend to be more often associated with positive emotions like happiness, while AI-generated texts tend to trigger negative emotions, particularly when inspired by specific literary movements and authors.